Reliability & construct validity of knowledge, attitude & practice of medical doctors on smoking cessation guidelines -The progress - Shalihin, Mohd Shaiful Ehsan; Md Aris, Mohd Aznan; Nik Mohamed, Mohamad Haniki; Mohd Rus, Razman; Jamani, Nurjasmine Aida (2016)
This study aimed to develop and validate a questionnaire to assess the knowledge, attitude and practice of medical doctors based on national smoking cessation guidelines and factors contributing to the score. 26 items consists of mixture of true/false choice questions and likert scaling response is validated and showed a high degree of internal consistency.